A numerical study of the effects of oxy-fuel combustion under homogeneous charge compression ignition regime. (April 2022) - Mobasheri, Raouf; Aitouche, Abdel; Peng, Zhijun; Li, Xiang
The European Union (EU) has recently adopted new directives to reduce the level of pollutant emissions from non-road mobile machinery engines. The main scope of project RIVER for which this study is relating is to develop possible solutions to achieve nitrogen-free combustion and zero-carbon emissions in diesel engines. RIVER aims to apply oxy-fuel combustion with Carbon Capture and Storage (CCS) technology to eliminate NOx emissions and to capture and store carbon emissions. As part of this project, a computational fluid dynamic (CFD) analysis has been performed to investigate the effects of oxy-fuel combustion on combustion characteristics and engine operating conditions in a diesel engine under Homogenous Charge Compression Ignition (HCCI) mode. A reduced chemical n-heptane-n-butanol-PAH mechanism which consists of 76 species and 349 reactions has been applied for oxy-fuel HCCI combustion modeling. Different diluent strategies based on the volume fraction of oxygen and a diluent gas has been considered over a wide range of air-fuel equivalence ratios. Variation in the diluent ratio has been achieved by adding different percentages of carbon dioxide for a range from 77 to 83 vol.% in the intake charge. Results show that indicated thermal efficiency (ITE) has reduced from 32.7% to 20.9% as the CO2 concentration has increased from 77% to 83% at low engine loads while it doesn't bring any remarkable change at high engine loads. It has also found that this technology has brought CO and PM emissions to a very ultra-low level (near zero) while NOx emissions have been completely eliminated.